TYPICAL AND ATYPICAL FORMS OF CELIAC DESEASE: DIFFICULTIES IN THE DIAGNOSIS - N. V. PORODENKO; V. V. SKIBITSKIY; V. V. ZAPEVINA; M. V. SKIBITSKAYA (Кубанский научный медицинский вестник, 2018)
The review analyzes materials devoted to the study of various forms of celiac disease. Particular attention is paid to the systematization of clinical manifestations and features of diagnosis of atypical forms of celiac disease. Data are given on the incidence and mechanisms of progression of disorders in the combination of celiac disease and a number of autoimmune diseases, including type 1 diabetes mellitus. This literature review promotes a better understanding of the problem of celiac disease by specialists, which will improve early diagnosis and determine the rational tactics of managing patients with different forms of the disease.